2022
DOI: 10.3389/fonc.2022.869752
|View full text |Cite
|
Sign up to set email alerts
|

The Global Impact of COVID-19 on Childhood Cancer Outcomes and Care Delivery - A Systematic Review

Abstract: BackgroundChildhood cancer represents a leading cause of death and disease burden in high income countries (HICs) and low-and-middle income countries (LMICs). It is postulated that the current COVID-19 pandemic has hampered global development of pediatric oncology care programs. This systematic review aimed to comprehensively review the global impact of COVID-19 on childhood cancer clinical outcomes and care delivery.MethodsA systematic search was conducted on PubMed, Embase, Medline, and the African Medical I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 95 publications
2
23
0
2
Order By: Relevance
“…However, still, some of the parents are reluctant to use healthcare facilities as their primary attempt due to negative parental perceptions regarding the quality of healthcare and national insurance. Our additional finding from qualitative data found that COVID‐19 pandemic affected healthcare facility accessibility due to lockdown and lack of family and community support groups 64 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, still, some of the parents are reluctant to use healthcare facilities as their primary attempt due to negative parental perceptions regarding the quality of healthcare and national insurance. Our additional finding from qualitative data found that COVID‐19 pandemic affected healthcare facility accessibility due to lockdown and lack of family and community support groups 64 …”
Section: Discussionmentioning
confidence: 90%
“…Our additional finding from qualitative data found that COVID-19 pandemic affected healthcare facility accessibility due to lockdown and lack of family and community support groups. 64 Certain limitations of this study need to be addressed. First, the cross-sectional study design may have potentially biased our results because of wide confounding factors, such as the high proportion of nonresponder subjects and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences were observed by geographical area, suggesting that the impact on cancer treatment, screening and diagnosis could depend on mitigation strategies countries implemented as well as on country-specific health care organization and resources. For example, shortage of treatment and delays and interruptions to cancer therapies in general were more pronounced in low-and middle-income countries 14 . The findings on disruption of cancer treatment, screening and diagnosis are in line with findings reported for other chronic diseases, such as cardiovascular disease 52 , suggesting the adverse impact might not be cancer specific.…”
Section: Discussionmentioning
confidence: 99%
“…Lignou S et al 2022 38 reported that between 18 th to 31 st of January 2021, pediatric and noncancer surgical activities were occurring at less than a third of the rate of the previous year, while Di Cosimo SD et al 2022 34 reported cancellation/delays of treatment in 58% (95%CI, 48%-67%; I 2 , 98%) of centers. Majeed A et al, 2022 14 showed that shortage of treatment and delays and interruptions to cancer therapies in general were more common in low-and middle-income countries.…”
Section: Delayed And/or Cancelled Treatmentmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) has caused tremendous strain on the healthcare systems worldwide and has captivated the interest of pediatric oncologists in a unique way. Adults with COVID-19 were reported to have a severe course of disease with a significantly higher mortality rate [ 2 ]. However, we now have data to show that most of the children who tested positive for COVID-19 had either asymptomatic infection or mild symptoms, with only a handful presenting with severe disease requiring critical care [ 3 ].…”
Section: Introductionmentioning
confidence: 99%